Speech-language pathology students' approaches to learning in a problem-based learning curriculum. - Mok CKF; Dodd B; Whitehill TL (International Journal of Speech-Language Pathology, 2009)
Problem-based learning (PBL) is hypothesized to enhance the development of deep learning. Most previous studies, however, have focused on outcomes (knowledge and skills) rather than students' approaches to learning, or how learning approach correlates with learning outcomes. Undergraduates in a speech-language pathology program (n = 114) completed the revised 2-factor Study Process Questionnaire (R-SPQ-2F) twice in an academic year to identify their approaches to learning and to compare these results with academic outcomes. Two findings emerged. Although the mean of scores for the deep approach (DA) to learning was consistently higher than the mean of scores for the surface approach (SA) to learning, exposure to PBL led to significant increase in DA and SA to learning during an academic year for students in Years 1 to 3. Students who did well in a PBL examination showed a much stronger DA than SA to learning, while students who performed less well showed a smaller difference between DA and SA to learning. Possible explanations for these findings are evaluated and implications for further studies are discussed.